2014
DOI: 10.5511/plantbiotechnology.13.1028a
|View full text |Cite
|
Sign up to set email alerts
|

Localization of transgene-derived friabilins in rice endosperm cells

Abstract: Puroindoline-a (Pina), puroindoline-b (Pinb) genes in the wheat hardness-locus region encode 15-kDa friabilin proteins, whose accumulation in the endosperm leads to grain softness texture. In wheat, the PINA and PINB friabilins are associated with starch granules in the endosperm cell, while there is no friabilin in rice. The rice endosperm structure consisting of compound starch granules is fundamentally different from that in wheat. We previously produced two different lines of transgenic rice plants with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Prior studies have identified unreduced PINs at 15 kDa, and the antibody probably did not react with PINs after reduction of disulphides or denaturation for immunocytochemical analyses, but the epitope recognised by this antibody has not been mapped (Greenwell, 1992;Wiley et al, 2007). Recently, this antibody has been used for immuno-localisation of PINs in the endosperm cells of transgenic rice, which found them localised between starch granules (Fujiwara et al, 2014). correct formation of tertiary structures in these methods, while the bioactivity was lost in denaturing conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have identified unreduced PINs at 15 kDa, and the antibody probably did not react with PINs after reduction of disulphides or denaturation for immunocytochemical analyses, but the epitope recognised by this antibody has not been mapped (Greenwell, 1992;Wiley et al, 2007). Recently, this antibody has been used for immuno-localisation of PINs in the endosperm cells of transgenic rice, which found them localised between starch granules (Fujiwara et al, 2014). correct formation of tertiary structures in these methods, while the bioactivity was lost in denaturing conditions.…”
Section: Discussionmentioning
confidence: 95%